Antibacterial activity of andrographis paniculata and euphorbia hirta methanol extracts - Ahmad Zorin Sahalan,; Nazahiyah Sulaiman,; Nihayah Mohammed,; Kaswandi Md. Ambia,; Hing, Hian Lian (Penerbit UKM, 2007)
Two species of plants, Andrographis paniculata and Euphorbia hirta were screened for antibacterial activities against three Gram positives and Gram negatives. The leaves from both plants were extracted by methanol extraction. The antibacterial activity was detected with spread plate well diffusion method. The extracts of both plants demonstrated inhibitory activity against both Gram negatives and positives bacteria. Staphylococcus aureus, Bacillus subtilis, Streptococcus epidemidis, Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa. The minimum inhibitory concentration (MIC) determination using micro dilution method showed that the MIC of A. paniculata for the tested bacteria were 1.56mg/ml (Staph. aureus), 3.13mg/ml (BAcillus subtilis), 3.13mg/ml (Strept. epidemidis), 1.56mg/ml (Escherichia coli), 12.50mg/ml (Klebsiella pneumoniae) and 3.13mg/ml (Pseudomonas aeruginosa)respectively. The MIC value for E. hirta was 6.25mg/ml (Staph. aureus) and 3.13mg/ml (BAcillus subtilis), 3.13mg/ml (Strept.Epidemidis), 3.13mg/ml (Psedomonas aeruginosa), 12.5mg/ml (Escherichia coli), and 6.25mg/ml (Klebsiella pneumoniae). Both plants represent a potential for pharmaceutical and agricultural applications and are worthy of further study.